Pengaruh Motivasi dan Kreativitas Praktik Terhadap Hasil Belajar Siswa pada Pembelajaran Instalasi Penerangan Listrik - Fahrezi Amran; Taali Taali (Jurnal Pendidikan Teknik Elektro, 2022)
This research was conducted with the aim of knowing how big the influence of learning motivation and practical creativity on students' practical learning outcomes in the subject of electrical lighting installation at SMK N 5 Padang. This type of research is quantitative research with correlation analysis method. The research subjects were students of class XII TITL 1 for questionnaire respondents and XI TITL 1 for the academic year 2021/2022 for practical learning outcomes. Data collection uses questionnaires and documentation, scoring the questionnaire instrument with a Likert scale and then the questionnaire is validated by an expert lecturer at the Department of Electrical Engineering before being tested and distributed to the main respondents. The data analysis technique used multiple linear regression analysis technique and hypothesis testing using t-test was conducted to partially test the effect between independent and dependent variables, and f-test was performed to test the effect simultaneously between independent and dependent variables. The results show that (1) there is a significant and positive influence on learning motivation on learning outcomes (2) there is a significant and positive influence on practical creativity on learning outcomes (3) there is a significant and positive influence on learning motivation and practical creativity together. on the learning outcomes of practical learning in the subject of Electrical Lighting Installation at SMK N 5 Padang.